Recovery of different types of hydroxyapatite by precipitation of phosphates of wastewater from anodizing industry. (1st January 2020) - Delgadillo-Velasco, Lorena; Hernández-Montoya, Virginia; Montes-Morán, Miguel A.; Gómez, Rigoberto Tovar; Cervantes, Francisco J.
Abstract: Recovery of phosphates from an anodizing industry wastewater was studied by chemical precipitation. Samples of wastewater were selected attending to the highest phosphate concentration observed during 1 year of weekly sampling. Different types of precipitant agents were analyzed in batch systems. Results showed that it is possible to remove 100 % of phosphates when Ca(OH)2 is used as precipitant agent. The best conditions of precipitation were found following a L9 orthogonal array design of the Taguchi method. For an initial concentration of phosphates of 4336  mg/L, these best conditions were a Ca/P molar ratio of 5.77, pH 2, stirring time of 15 min and settling time of 1 h. Additionally, it was demonstrated that the factors with more influence in the precipitation of phosphates with Ca(OH)2 were the pH of the wastewater and the stirring time. When the phosphate removal was performed at pH 6 and 10, hydroxyapatite Ca5 (PO4 )3 (OH) was found in the precipitate, whereas other crystalline hydroxyapatite with a more complex structure (Ca3.36 Na0.08 )(Ca5.04 Na0.72 )(PO4 )3.6 (CO3 )2.4 (OH)2 was identified in the experiment performed at pH 2. The present study provides valuable information to recover phosphate from industrial effluents. Graphical abstract: Image 1099 Highlights: 100% of phosphates removed from anodizing industry wastewater. Taguchi method can be used to optimize the precipitation of phosphates. Ca(OH)2 was the most effective precipitant agent of phosphates. Phosphates were recovered as different types of hydroxyapatite.